The role of beliefs and norms in consumer environmental behavior: an empirical study in the context of organic products - Mora Román, Marly Fernanda; Bonisoli, Lorenzo (mktDESCUBRE; Vol 1 No 21 (2023): Twenty-first Edition (January - June), 2023)
Given the global environmental problems, research on pro-environmental behaviors is becoming increasingly relevant. The purpose of this study is to analyze the factors that influence consumers' environmental behavior. To achieve this, a theoretical model integrating the Norm Activation Theory (NAT) and environmental beliefs has been developed. For the empirical analysis, a questionnaire was administered to 419 consumers of organic products, and the SEM-PLS technique was employed for data analysis. The results indicate that all the proposed hypotheses are accepted, and the R 2 and Q 2 value of the endogenous variables is found to be weak to moderate. Therefore, it can be concluded that beliefs and norms are valid predictors of environmental behavior, and future research could further expand the analysis by incorporating other aspects, such as consumer values.